Genetic refinement and physical mapping of the CMT4B gene on chromosome 11q22. - Bolino, A; Levy, E; Muglia, M; Conforti, F; LeGuern, E; Salih, M; Georgiou, D; Christodoulou, R; Hausmanowa-Petrusewicz, I; Mandich, P; Gambardella, A; Quattrone, A; et al. (2000)
Charcot-Marie-Tooth disease type 4B (CMT4B) is a demyelinating autosomal recessive motor and sensory neuropathy characterized by focally folded myelin sheaths in the peripheral nerve. We recently mapped the CMT4B gene to a 5-cM interval on chromosome 11q22, using homozygosity mapping and haplotype sharing analysis on a large inbred pedigree. In the present study, we report the construction of a YAC-based transcript map across the 5-cM critical region, including 26 YACs, 35 STSs, and 52 ESTs. Furthermore, using 15 additional physically ordered microsatellite markers from the 11q22 region on the original inbred family, we were able to narrow the critical interval for the gene to 2 Mb, which is now flanked by markers D11S1757 and CHLC-GATA3B05. Finally, after computer analysis of the 33 ESTs assigned to the 2-Mb interval, we demonstrated that 21 different transcripts as well as 3 known genes might represent potential candidates for the disease.